MXene-enhanced CO₂ sensors: a comprehensive review on mechanisms, challenges, and environmental impact - Nibedita Nath; Subhendu Chakroborty; Trishna Bal; Rashmi Chourasia; Amiya Ranjan Panda; Pradeep Kumar Pandey; Bhanu Pratap Singh; Ratan Kumar Dey; Jitendra Malviya; Chandra Chakraborty (Discover Applied Sciences)
Abstract MXenes are a burgeoning category of two-dimensional materials with many possible uses, such as gas sensing, energy storage, biological applications, and catalysis. The gas-sensing use of MXene materials is now receiving significant interest in academic research due to their heightened sensitivity toward a wide range of gases. However, this particular application remains relatively unexplored in the scientific community. Graphene has been identified as a very suitable host material for chemical gas sensors because of its several advantageous properties. These properties include a large surface area, strong electrical conductivity, and abundant surface functional groups. The carbon dioxide (CO2) escalation has deleterious consequences for the environment, human well-being, and agricultural output. Hence, it is important to employ diverse methodologies to monitor the content of CO2 with high responsiveness. This study examines the advancements in Mxene-based nanomaterials as sensors for detecting CO2. This section will address the challenges and potential prospects of gas sensors utilizing Mxene materials.